Supporting Applied, Multidisciplinary Analytic Skills: An Innovative Training Platform for Researcher Capacity Building - Greenwood, Ann (International Journal of Population Data Science, 2018)
Overview Population Health Research is inherently interdisciplinary, multifaceted and firmly rooted in the evolving connections between place, time and related socioeconomic processes. To excel in this rapidly diversifying field, individuals require a broad range of multidisciplinary skills gained through applied, collaborative and real world learning environments. Objective To serve the emerging multidisciplinary skills and capacity building needs of Population Health Researchers within a rapidly diversifying field. Approach Establishment of an innovative research training platform that supports skill development in an accessible, collaborative and applied learning environment. Designed in collaboration with a multi-university research platform, this fully online practice-based training environment both mirrors and supports many of the day to day skill development needs of health and social science researchers. Results Now in its 6th year of delivery, the multidisciplinary focus of this specialized training platform is successfully addressing the skill development needs of a diverse cross section of health research professionals. Trainees are bringing a wealth of experience and knowledge to share with their online colleagues, supporting a rich, practice based education and skills development environment. Those enrolled in the program possess backgrounds ranging from Population and Public Health, Epidemiology, Statistics and Sociology to Medicine to Psychology, Geography, Biostatistics and International Health. Graduates of the program are gaining skills that benefit their research and careers. Lessons learned with respect to the development of the training platform and capacity building skills achieved by program graduates will be outlined. Conclusion/Implications Providing timely, practical, hands-on analytic skills training is critical to building the capacity of new and mid-career researchers and health professionals. Direct application of these new skills is an essential outcome and best measure of success. We are listening to our trainees and learning as we grow. Learn more here.